Composite plugging agent and application thereof
By providing a composite charter containing elastic particles, rigid particles, flexible fibers, and rigid sheet materials, the existing leakage agent cannot meet the high -acid solubility and high pressure of high -acid solubility and high pressure pressure of carbonate rock caves. The problem has achieved effective protection and efficient blocking of carbonate rock strata.
Patent Information
- Application Number
- CN202310925213.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-26
- Publication Date
- 2025-01-28
AI Technical Summary
The existing leak plugging agent cannot meet the high acid-soluble and high pressure-bearing leakage requirements of carbonate rock crack hole formation leakage, and cannot take into account both safe construction, efficient sealing and reservoir protection.
A compound blocker, including elastic particles, rigid particles, flexible fibers, and rigid sheet -like materials, which can form a highly underwriting temporary shielding layer.
The effective protection of carbonate rock strata has been realized, has high acid solubility and high pressure, can adapt to leakage channels of different sizes, improve the success rate of leakage, and reduce the time leakage treatment time.
Smart Images

Figure CN119371947A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of plugging leaks in oil or natural gas drilling, and in particular relates to a composite plugging agent and application thereof. Background Art
[0002] The proven reserves of carbonate oil and gas reservoirs account for more than 50% of the total oil and gas resources, of which more than 30% are fracture-cavity oil and gas reservoirs, with huge development potential. Fracture-cavity oil and gas reservoirs are prone to leakage of varying degrees or even malignant leakage due to the development of fractures and caves and strong heterogeneity, and the randomness of leakage during reservoir drilling. Reservoir plugging materials must meet the requirements of high acid solubility, high temperature resistance, high pressure bearing, and strong adaptability to leaking layers. However, the types of acid-soluble materials commonly used on site, such as ultrafine calcium carbonate and calcite, are limited, and the plugging characteristics are single. It is impossible to take into account the requirements of safe construction, efficient plugging and reservoir protection at the same time, and the technology and performance need to be further improved. Therefore, it is urgent to develop a plugging agent with high acid solubility, high pressure bearing, excellent performance and strong adaptability for leakage in carbonate fracture-cavity formations, so as to achieve effective retention, form a high-pressure temporary plugging shielding layer, reduce the risk of well leakage, restore the oil and gas channel after acidification and unblocking, and achieve effective protection of the oil and gas layer. Summary of the invention
[0003] In order to solve the problem that existing plugging agents cannot meet the high acid solubility and high pressure plugging requirements of carbonate rock fracture and cave formation leakage, the present invention provides a composite plugging agent and its application, which can form a high-pressure temporary plugging shielding layer, restore the oil and gas channel after acidification and unblocking, and achieve effective protection of the oil and gas layer.
[0004] The invention provides a composite plugging agent, which comprises elastic particles, rigid particles, flexible fibers and rigid sheet materials.
[0005] In a specific embodiment of the present invention, based on the weight of the composite plugging agent, the composite plugging agent comprises:
[0006]
[0007] In one embodiment of the present invention, the elastic particles include a polymer and an inorganic filler;
[0008] Preferably, taking the mass of the elastic particles as 100%, the elastic particles include 28.5wt% to 55.5wt% of polymer and 44.5wt% to 71.5wt% of inorganic filler;
[0009] Preferably, the schematic structural formula of the polymer is as shown in Formula I:
[0010]
[0011] Wherein, R1 is -CONHC(CH3)2CH2SO3Na or -COONa; R2 is at least one of -CONH2, -CON(CH3)2 and -CON(CH2CH3)2; R3 is -CONHCH2NHCO-;
[0012] m, n, o, p and q are respectively the amounts of substances of each monomer unit in the polymer, and taking the sum of m, n, o, p and q as 100%, the ratios of m, n, o, p and q are (0.001 to 0.002):(0.1 to 0.2):(0.06 to 0.1):(0 to 0.08):(0 to 0.06); and / or
[0013] The inorganic filler is bluestone powder and / or first calcium carbonate particles;
[0014] Preferably, the weight average molecular weight of the polymer is 1.5 million to 2.5 million; and / or
[0015] The particle size of the inorganic filler is 8 μm to 75 μm.
[0016] Formula I only reflects the types of monomer units in the polymer and the substance amount relationship of each monomer unit, and does not represent the specific structure of the polymer.
[0017] In a specific embodiment of the present invention, the rigid particles are second calcium carbonate particles.
[0018] In a specific embodiment of the present invention, the flexible fiber is selected from at least one of plant fiber (such as wood fiber, corn fiber, bamboo fiber), asbestos wool, sepiolite fiber and silicate fiber.
[0019] In a specific embodiment of the present invention, the rigid sheet material is selected from at least one of oyster shells, shell residues and mica sheets.
[0020] In a specific embodiment of the present invention, the particle size of the elastic particles is 1 mm to 3 mm; and / or the particle size of the rigid particles is 8 μm to 75 μm.
[0021] In a specific embodiment of the present invention, the length of the flexible fiber is 0.1 mm to 1 mm.
[0022] In a specific embodiment of the present invention, the length of the rigid sheet material at the maximum diameter is 1 mm to 3 mm.
[0023] In a specific embodiment of the present invention, the elastic particles are prepared by:
[0024] a. mixing an acrylic monomer, an acrylamide monomer, a crosslinking agent, an inorganic filler and water to obtain a reaction solution;
[0025] b. deoxygenating the reaction solution, adding an initiator, reacting the acrylic monomer, the acrylamide monomer and the crosslinking agent to obtain a polymer, and granulating to obtain the elastic particles.
[0026] In a specific embodiment of the present invention, the molar ratio of the acrylic monomer, the acrylamide monomer and the crosslinking agent is (0.05 to 0.2): (0.05 to 0.1): (0.001 to 0.006);
[0027] Preferably, the molar ratio of the acrylic monomer, the acrylamide monomer and the cross-linking agent is (0.05 to 0.2):(0.05 to 0.1):0.001.
[0028] In a specific embodiment of the present invention, the amount of the initiator is 0.19 wt % to 0.31 wt % based on the total weight of the acrylic monomer, the acrylamide monomer and the crosslinking agent; and / or
[0029] Based on the total mass of the acrylic monomer, acrylamide monomer, crosslinking agent, initiator and inorganic filler, the total amount of the acrylic monomer, acrylamide monomer and crosslinking agent is 28.5wt% to 55.5wt%; the amount of the inorganic filler is 44.5wt% to 71.5wt%.
[0030] In a specific embodiment of the present invention, the acrylic monomer is acrylic acid or 2-acryloyl-2-methylpropanesulfonic acid; and / or
[0031] The acrylamide monomer is selected from at least one of acrylamide, N,N-dimethylacrylamide and N,N-diethylacrylamide; and / or
[0032] The cross-linking agent is a water-soluble cross-linking agent; and / or
[0033] The initiator includes an oxidizing agent and a reducing agent;
[0034] Preferably, the water-soluble cross-linking agent is N,N-methylenebisacrylamide;
[0035] Preferably, the molar ratio of the oxidizing agent to the reducing agent is 1:1;
[0036] Preferably, the oxidizing agent is a persulfate (eg potassium persulfate or ammonium persulfate); and / or
[0037] The reducing agent is a sulfite (eg, at least one of sodium sulfite, potassium sulfite and ammonium sulfite) or a bisulfite (eg, at least one of sodium bisulfite, potassium bisulfite and ammonium bisulfite).
[0038] In a specific embodiment of the present invention, in step b, the pH of the reaction solution is adjusted to 9 to 11, deoxygenated, an initiator is added, acrylic monomers, acrylamide monomers and a crosslinking agent are reacted to obtain a polymer, which is then dried and granulated to obtain the elastic particles.
[0039] In one embodiment of the present invention, in step b, the reaction temperature is 35°C to 65°C;
[0040] and / or
[0041] The reaction time is 2h to 4h; and / or
[0042] The drying temperature is 100°C to 110°C;
[0043] Preferably, the pH of the reaction solution is adjusted with an inorganic base (eg, at least one of sodium hydroxide, potassium hydroxide and aqueous ammonia).
[0044] The composite plugging agent provided by the invention is used in oil or natural gas drilling, especially in plugging leaks in carbonate rock fracture-cavity formations.
[0045] Beneficial effects of the present invention:
[0046] In view of the limited types of acid-soluble plugging materials in the prior art, the single plugging characteristics, and the inability to take into account the requirements of safe construction, efficient plugging and reservoir protection at the same time, the present invention provides a composite plugging agent and its application. The composite plugging agent includes elastic particles, rigid particles, flexible fibers and rigid sheet materials, which have the functions of rigid bridging, deformation filling, and meshing reinforcement, and has good adaptive ability for leakage channels of different sizes (0.5mm to 5mm) in carbonate formations, and the temperature resistance reaches 150°C. The plugging layer is stable under high temperature and high pressure, and the plugging pressure bearing capacity can reach more than 20MPa, and will not be squeezed and damaged to reduce the plugging strength, thereby improving the one-time plugging success rate and reducing the well leakage treatment time; the acid solubility in 15wt% hydrochloric acid aqueous solution exceeds 85%, which is conducive to on-site acidification and plugging, and protects the reservoir, and is suitable for well leakage treatment and reservoir protection during reservoir drilling and completion; in addition, the composite plugging agent provided by the present invention is prepared on-site, safe and simple to operate, and meets the requirements of on-site plugging. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the infrared spectrum of the polymer in the elastic particles prepared in Example 3. DETAILED DESCRIPTION
[0048] The present invention will be further described below in conjunction with examples, but the examples of the present invention are only exemplary descriptions, and the implementation manner does not constitute a limitation of the present invention under any circumstances.
[0049] Preparation of elastic particles
[0050] Bluestone powder (particle size 48 to 75 μm): purchased from Lingshou County Mineral Factory;
[0051] Calcium carbonate particles (particle size 8 to 75 μm): purchased from Lingshou County Mineral Factory.
[0052] Example 1
[0053] 10.35g of AMPS (2-acryloyl 2-methylpropanesulfonic acid), 3.554g of AM (acrylamide), and 0.15g of N,N-methylenebisacrylamide were added to 100g of clean water and fully dissolved. Then, 35g of bluestone powder with a particle size of 48 to 75μm was added, and after stirring evenly, the pH was adjusted to 9 with an aqueous sodium hydroxide solution (wherein the concentration of sodium hydroxide was 1mol / L). When the temperature was raised to 35°C, 0.027g of potassium persulfate and 0.01g of sodium sulfite were added. AMPS, AM and N,N-methylenebisacrylamide were allowed to react for 2h to generate a polymer with a schematic structural formula of Formula II (Formula II only reflects the type of monomer units in the polymer prepared in this embodiment and the substance amount relationship of each monomer unit, and does not represent the specific structure of the polymer). The product was taken out, dried at 100°C, and granulated to obtain elastic particles with a particle size of 1 to 3mm.
[0054]
[0055] Example 2
[0056] 14.212 g of AA (acrylic acid), 7.108 g of AM (acrylamide), and 0.15 g of N,N-methylenebisacrylamide were added to 100 g of clean water to fully dissolve, and then 20 g of calcium carbonate particles with a particle size of 8 to 75 μm were added. After stirring evenly, the pH was adjusted to 11 with an aqueous sodium hydroxide solution (wherein the concentration of sodium hydroxide was 1 mol / L). When the temperature was raised to 65° C., 0.046 g of ammonium persulfate and 0.021 g of sodium bisulfite were added. AA, AM and N,N-methylenebisacrylamide were allowed to react for 4 hours to generate a polymer having a schematic structural formula of Formula III (Formula III only reflects the type of monomer units in the polymer prepared in this embodiment and the substance amount relationship of each monomer unit, and does not represent the specific structure of the polymer). The product was taken out, dried at 110° C., and granulated to obtain elastic particles with a particle size of 1 to 3 mm.
[0057]
[0058] Example 3
[0059] 20.7g AMPS (2-acryloyl-2-methylpropanesulfonic acid), 2.13g AM (acrylamide), 3.97g N-N-dimethylacrylamide, 3.81g N,N-diethylacrylamide and 0.15g N,N-methylenebisacrylamide were added to 100g clean water and fully dissolved. Then, 10g bluestone powder with a particle size of 48 to 75μm and 15g calcium carbonate particles with a particle size of 8 to 75μm were added, stirred evenly, and the pH was adjusted to 50 with sodium hydroxide aqueous solution (wherein the concentration of sodium hydroxide was 1mol / L). 10. When the temperature is raised to 65° C., 0.041 g of potassium persulfate and 0.02 g of sodium sulfite are added, and AMPS, AM, NN-dimethylacrylamide, N,N-diethylacrylamide and N,N-methylenebisacrylamide are allowed to react for 3 h to generate a polymer having a schematic structural formula of Formula IV (Formula IV only reflects the types of monomer units in the polymer prepared in this embodiment and the substance amount relationship of each monomer unit, and does not represent the specific structure of the polymer). The product is taken out, dried at 105° C., and granulated to obtain elastic particles with a particle size of 1 to 3 mm.
[0060]
[0061] Preparation of composite plugging agent
[0062] Sepiolite fiber (fiber length 0.1 to 1 mm): purchased from Shijiazhuang Fucheng Mineral Products Co., Ltd.;
[0063] Silicate fiber (fiber length 0.1 to 1 mm): purchased from Shijiazhuang Fucheng Mineral Products Co., Ltd.;
[0064] Calcium carbonate particles (particle size 8 to 75 μm): purchased from Lingshou County Mineral Factory;
[0065] Shell residue, oyster shell (length at the maximum diameter is 1 to 3 mm): generally available in the market.
[0066] Example 4
[0067] 30 g of the elastic particles prepared in Example 1, 50 g of calcium carbonate particles with a particle size of 8 to 75 μm, 10 g of sepiolite fibers with a fiber length of 0.1 to 1 mm, and 10 g of shell residue with a maximum diameter of 1 to 3 mm are mixed evenly to obtain a composite plugging agent.
[0068] Example 5
[0069] 35 g of the elastic particles prepared in Example 2, 40 g of calcium carbonate particles with a particle size of 8 to 75 μm, 5 g of silicate fibers with a fiber length of 0.1 to 1 mm, and 20 g of oyster shells with a maximum diameter of 1 to 3 mm were mixed evenly to obtain a composite plugging agent.
[0070] Example 6
[0071] 40 g of the elastic particles prepared in Example 3, 45 g of calcium carbonate particles with a particle size of 8 to 75 μm, 5 g of sepiolite fibers with a fiber length of 0.1 to 1 mm, and 10 g of oyster shells with a maximum diameter of 1 to 3 mm were mixed evenly to obtain a composite plugging agent.
[0072] Experimental evaluation
[0073] 1. Characterization of polymers in elastic particles
[0074] The infrared spectra of the polymers in the elastic particles prepared in Examples 1 to 3 were measured using a Fourier transform infrared spectrometer, and Example 3 is taken as an example for illustration.
[0075] The elastic particles prepared in Example 3 were demulsified with anhydrous ethanol, then washed with anhydrous ethanol for 8 hours in a Soxhlet extraction apparatus, dried and ground, and analyzed by infrared spectroscopy. The results are shown in FIG. Figure 1 .Depend on Figure 1 It can be seen that the spectrum wave number is 3438cm -1 A broad peak appears at 2938-1667 cm-1. The absorption peak here is caused by the symmetrical stretching vibration of the NH bond in the polyacrylamide molecule. -1 There are two weaker characteristic absorption peaks at 1224cm -1 1046cm -1 Two weaker absorption peaks appear at , which are caused by the antisymmetric stretching vibration of the O=S=O bond. Based on the above analysis results of each characteristic absorption peak in the infrared spectrum, it can be verified that the synthetic product contains the structure of sulfonate and acrylamide.
[0076] 2. Determination of acid solubility of elastic particles and composite plugging agents
[0077] 1) Preparation of samples to be tested: The elastic particles prepared in Examples 1 to 3 were crushed through a 60-mesh sieve, dried at 105±3° C., and then cooled to obtain samples 1 to 3 to be tested;
[0078] The composite plugging agents prepared in Examples 4 to 6 were crushed and passed through a 60-mesh sieve, dried at 105±3° C., and then cooled to obtain test samples 4 to 6;
[0079] 2) Acid solubility determination:
[0080] ⅰ Weigh 2g of the sample to be tested (accurate to 0.0001g) into a 250mL stoppered conical flask, add 100mL of 15wt% hydrochloric acid aqueous solution, shake well and place in a constant temperature water bath at 90±2℃ for 4h. During the reaction, shake once every 15min, and each time for no less than 10min;
[0081] ii) Filter with medium-speed quantitative filter paper of known mass after drying, rinse the conical flask with distilled water so that all the residue is transferred to the filter paper, and rinse the residue with distilled water until there is no chloride ion (check with 1wt% silver nitrate solution);
[0082] ⅲ Place the filter paper and the residue on a dry surface dish, dry at 105±3℃ to constant weight, take out and place in a desiccator to cool for 30 minutes, then weigh it and calculate the acid solubility of the sample to be tested:
[0083] Acid solubility = (weight of sample to be tested - weight of acid-insoluble substances) / weight of sample to be tested × 100%;
[0084] The acid solubility of the samples 1 to 6 was determined according to the above method.
[0085] The specific results are shown in Table 1.
[0086] Table 1. Acid solubility of elastic particles and composite plugging agents
[0087]
[0088]
[0089] It can be seen from the data in Table 1 that although the acid solubility of the composite plugging agent prepared in Examples 4 to 6 in 15 wt % hydrochloric acid aqueous solution is slightly lower than that of the elastic particles prepared in Examples 1 to 3, it is still above 85%, meeting the technical requirements for reservoir protection.
[0090] 3. Evaluation of the plugging performance of composite plugging agents
[0091] The plugging performance of the composite plugging agents prepared in Examples 4 to 6 was evaluated using a crack plugging simulation device, which mainly consists of a continuously variable speed displacement pump, a simulated tempered wellbore and a crack module. The crack module is made by milling and splitting a steel column. The length of the crack module is 15 cm. By combining different modules, the device can simulate cracks with a width of 0.1 to 5 mm.
[0092] Bentonite: purchased from Lingshou County Yuchuan Mineral Products Co., Ltd.;
[0093] Soda ash (Na2CO3): purchased from Suzhou Moxuan Chemical Technology Co., Ltd.
[0094] 1) Prepare bentonite-based slurry: add soda ash and bentonite to 1L of water, stir thoroughly, and obtain bentonite slurry (wherein the mass fraction of soda ash is 8wt%, and the mass fraction of bentonite is 0.24wt%). Curing the bentonite slurry at room temperature (25°C) for 4 to 10h, diluting with water, and obtaining a bentonite-based slurry with a total mass concentration of bentonite and soda ash of 4wt%;
[0095] 2) Preparation of plugging slurry: 300 mL of the bentonite-based slurry prepared in step 1) was mixed with the composite plugging agent prepared in the embodiment of the present invention to obtain plugging slurries with a composite plugging agent mass concentration of 25%, 30%, and 35%;
[0096] The composite plugging agents prepared in Examples 4 to 6 were used to prepare plugging slurries according to the method described in step 2) to carry out crack plugging experiments. The widths of the cracks were 0.5 mm, 1 mm, 3 mm, and 5 mm, and the length of the cracks was 15 cm.
[0097] 3) Leakage plugging experiment:
[0098] ⅰInstall the fracture module from the bottom of the simulated toughened wellbore of the fracture plugging simulation device, tighten the lower steel cover, and close the lower steel cover ball valve;
[0099] ⅱ After pouring 30mL of 4wt% bentonite-based slurry into the simulated cracks of the steel cylinder, pour 300mL of the prepared plugging slurry along the inner wall of the steel cylinder to prevent mixing of the slurry and affect the plugging effect, tighten the upper steel cover, connect the high-pressure pipeline, tighten the conversion joint, and open the lower steel cover ball valve;
[0100] ⅲ Open the pump at full displacement, observe the pressure change, and record the relationship between the leakage and the pressure bearing capacity (stop the experiment when the plugging slurry is squeezed out or the pressure bearing capacity reaches the limit value of 20MPa);
[0101] ⅳAfter the experiment is completed, the leakage volume is measured and the maximum pressure bearing capacity is recorded. The experimental results are shown in Table 2.
[0102] Table 2. The plugging ability of plugging slurries with different concentrations containing different composite plugging agents on cracks of different widths
[0103]
[0104]
[0105] It can be seen from the data in Table 2 that the composite plugging agent prepared in Examples 4 to 6 can plug cracks with a width of 0.5 to 5 mm, and the positive pressure bearing capacity is not less than 18 MPa. As the crack width decreases, although the positive pressure bearing capacity increases, there is a certain sealing phenomenon, which is not conducive to the plugging material entering the leaking layer to form a plug; as the crack width increases, the positive pressure bearing capacity does not decrease significantly, but the plugging layer formed in the crack is longer, and the plugging layer is continuously compacted under the action of the pressure difference, and the plugging layer is more stable. At the same time, the plugging agent provided by the present invention is prepared at the site of use, the on-site operation process is safe, the leaking layer has good adaptability, and the plugging success rate can be effectively guaranteed.
[0106] 3. High temperature resistance of composite plugging agent
[0107] The plugging layer formed by the plugging slurry containing the composite plugging agent in the fracture block in Experiment 2 was aged at 150°C for 24 h, and then displaced with a high-pressure metering pump, and the changes in the plugging pressure bearing capacity were recorded, as shown in Table 3.
[0108] Table 3. The plugging pressure bearing capacity of the plugging layer after 24h of airtight aging at 150℃
[0109]
[0110]
[0111] It can be seen from the data in Table 3 that the plugging layers formed by the plugging slurries of different mass concentrations prepared by the composite plugging agents prepared in Examples 4 to 6 in crack blocks of different widths have basically no decrease in plugging pressure bearing capacity after being cured at 150°C for 24 hours, proving that the composite plugging agents prepared in Examples 4 to 6 are temperature resistant up to 150°C.
[0112] Although the present invention has been described with reference to specific embodiments, it will be appreciated by those skilled in the art that various changes may be made without departing from the true spirit and scope of the present invention. In addition, the subject matter, spirit and scope of the present invention may be varied to accommodate specific situations, materials, material combinations and methods. All of these changes are included within the scope of the claims of the present invention.
Claims
1. A composite plugging agent, comprising elastic particles, rigid particles, flexible fibers and rigid sheet materials.
2. The composite plugging agent according to claim 1, characterized in that: Based on the weight of the composite plugging agent, the composite plugging agent comprises:
3. The composite plugging agent according to claim 1 or 2, characterized in that: The elastic particles include polymer and inorganic filler; Preferably, taking the mass of the elastic particles as 100%, the elastic particles include 28.5wt% to 55.5wt% of polymer and 44.5wt% to 71.5wt% of inorganic filler; Preferably, the schematic structural formula of the polymer is as shown in Formula I: Wherein, R1 is -CONHC(CH3)2CH2SO3Na or -COONa; R2 is at least one of -CONH2, -CON(CH3)2 and -CON(CH2CH3)2; R3 is -CONHCH2NHCO-; m, n, o, p and q are respectively the amounts of substances of each monomer unit in the polymer, and taking the sum of m, n, o, p and q as 100%, the ratios of m, n, o, p and q are (0.001 to 0.002):(0.1 to 0.2):(0.06 to 0.1):(0 to 0.08):(0 to 0.06); and / or The inorganic filler is bluestone powder and / or first calcium carbonate particles; and / or The particle size of the inorganic filler is 8 μm to 75 μm.
4. The composite plugging agent according to any one of claims 1 to 3, characterized in that: The rigid particles are second calcium carbonate particles.
5. The composite plugging agent according to any one of claims 1 to 4, characterized in that: The flexible fiber is selected from at least one of plant fiber, asbestos wool, sepiolite fiber and silicate fiber.
6. The composite plugging agent according to any one of claims 1 to 5, characterized in that: The rigid sheet material is selected from at least one of oyster shells, shell residues and mica sheets.
7. The composite plugging agent according to any one of claims 1 to 6, characterized in that: The particle size of the elastic particles is 1 mm to 3 mm; and / or the particle size of the rigid particles is 8 μm to 75 μm.
8. The composite plugging agent according to any one of claims 1 to 7, characterized in that: The length of the flexible fiber is 0.1 mm to 1 mm.
9. The composite plugging agent according to any one of claims 1 to 8, characterized in that: The length of the rigid sheet material at the maximum diameter is 1 mm to 3 mm.
10. Use of the composite plugging agent according to any one of claims 1 to 9 in oil or gas drilling, especially in plugging leaks in carbonate rock fracture-cavity formations.
Citation Information
Patent Citations
Controllable expanded plugging agent
CN102146280A
Acid-soluble composite plugging agent and application thereof
CN104119847A
Multi-element synergic plugging agent and application thereof
CN104232039A
Plugging agent and preparation method of same
CN105238373A
Formula for well drilling leaking stoppage
CN111574974A
Cited By
Plugging agent suitable for malignant leakage formation as well as preparation method and application of plugging agent
CN120590929A